EDUCATION AND LIBERATION - Austin, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
ABSTRACT. Drawing on his personal experience as a university student in the 1990s as well as those of a little-known 1960s Montreal-based group, the Caribbean Conference Committee, Austin calls for a return of community education and to the idea that education has meaning and value on its own term. He argues that the joining of theory with practice represents a powerful tool in the struggle for social and economic justice and transformation. ÉDUCATION ET LIBÉRATION RÉSUMÉ. S’appuyant sur son expérience d’étudiant universitaire dans les années 1990 ainsi que sur l’histoire d’un groupe des années 1960 méconnu, le Caribbean Conference Committee, Austin préconise le retour à une éducation communautaire et la revalorisation du processus éducationnel comme activité porteuse de sens et de valeurs. Austin avance qu’allier la théorie et la pratique peut s’avérer un outil percutant dans la lutte pour la transformation et la justice sociale et économique.